What Drives Inflation Expectations in Brazil? : An Empirical Analysis - Cerisola, Martin (IMF Working Papers; Working Paper, 2005)
This study examines the macroeconomic determinants of survey inflation expectations in Brazil since the adoption of inflation targeting in 1999. The results suggest that the inflation targeting framework has helped anchor expectations, with the dispersion of inflation expectations declining considerably, particularly during periods of high uncertainty. We also find that apart from the inflation target, the stance of fiscal policy, as proxied by the ratio of the consolidated primary surplus to GDP, has been instrumental in shaping expectations. The importance of past inflation in determining expectations appears to be relatively low, and the overall empirical evidence does not suggest the presence of substantial inertia in the inflation process.